Improvement of Sugarcane Leaves Property by Torrefaction in a Continuous Flow Reactor - Pattiya, Adiak (Srinakharinwirot University Engineering Journal, 2019)
In this paper, torrefaction of sugarcane leaves was carried out in a lab-scale 600 g/h continuous flow pyrolysis reactor with an aim to improve the biomass heating value with minimum weight loss and minimum reaction time. The effects of torrefaction temperature (260, 280 and 300°C) and solid residence time (1, 3 and 5 min) were investigated to determine the mass and energy yields, the heating value and the energy densification of the torrefied biomass. The results show that, within the ranges of the parameters studied, the mass yields of 68-89 wt% on dry basis were obtained, corresponding to the energy yields of 84-95%. The higher heating values of the torrefied sugarcane leaves were in the range of 19-21 MJ/kg compared to 17.5 MJ/kg for the original biomass. This corresponds to the energy densification of 1.06-1.21. The torrefaction conditions that gave the highest torrefied biomass heating value and energy densification were 280°C and 5 minutes.